Analysis and proposed organization of the capoeira song repertoire (2006)
In this paper, the lyrics of Capoeira songs are used as areliable source of information about the most importantaspects of this art-form: music, ritual, play, history, philosophyand the idiosyncrasy of its practitioners. Thispaper elucidates the musical universe of Capoeira througha systematic analysis of the lyrics of a selected group ofsongs. The songs are classified using two criteria andboth criteria are analyzed. Furthermore, certain aestheticelements of the music are studied to complement thediscussion of the lyrics.